FOP Negatively Regulates Ciliogenesis and Promotes Cell Cycle Re-entry by Facilitating Primary Cilia Disassembly - Jiang, Huadong; Liu, Shanshan; Cheung, Man-Hei; Amin, Aftab; Liang, Chun (Frontiers in Cell and Developmental Biology, 2020)
Primary cilia are microtubule-based, antenna-like organelles, which are formed in G0 phase and resorbed as cells re-enter the cell cycle. It has been reported that primary cilia can influence the timing of cell cycle progression. However, the molecular links between ciliogenesis and cell cycle progression are not well understood. The Fibroblast Growth Factor Receptor 1 Oncogene Partner (FOP) has been implicated in ciliogenesis, but its function in ciliogenesis is not clear. Here, we show that FOP plays a negative role in ciliogenesis. Knockdown of FOP promotes cilia elongation and suppresses cilia disassembly. In contrast, ectopic expression of FOP induces defects in primary cilia formation, which can be rescued by either pharmacological or genetic inhibition of Aurora kinase A which promotes cilia disassembly. Moreover, knockdown of FOP delays cell cycle re-entry of quiescent cells following serum re-stimulation, and this can be reversed by silencing Intraflagellar Transport 20 (IFT20), an intraflagellar transport member essential for ciliogenesis. Collectively, these results suggest that FOP negatively regulates ciliogenesis and can promote cell cycle re-entry by facilitating cilia disassembly.